A Temporal Approach to Retrenchment and Successful Turnaround in Declining Firms. (30th April 2015) - Tangpong, Chanchai; Abebe, Michael; Li, Zonghui
Abstract This study extends current understanding of the retrenchment–turnaround relationship in declining firms by introducing a temporal approach and arguing that the effectiveness of retrenchment as a strategy is contingent on its adoption early in turnaround attempts. Drawing from the two‐stage turnaround model and insights from the literature on downward spirals in organizations, we develop and test a theoretical model that explains how temporal considerations in retrenchment influence the likelihood of successful turnaround. Using a matched pair sample of 96 US firms, we find that declining firms that implement retrenchment actions early have a higher likelihood of successful turnaround. The findings also indicate that while two specific retrenchment actions, early divestments and early geographic market exits, significantly contribute to the likelihood of successful turnaround, early layoffs do not. Overall, the findings shed some light on the importance of timing strategic actions in organizational turnarounds. Implications for research and practice are discussed.